Pola dan Perkembangan Perbankan Syariah di Indonesia - Ahmad Khoirin Andi (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2019)
The development of Islamic banking in Indonesia with the complexity of the problem in its journey has shown good results and as a reference for the pattern and strategy for developing financial institutions. Islamic banking with its (the) sharia principles of avoiding usury practices and prioritizing mutual benefits have proven to be a complete banking system. But besides that, additional supervision is needed to ensure the implementation of sharia principles, namely by the existence of a sharia supervisory board (DPS) to implement fatwas as guidelines for the operation of Islamic banks issued by the National Sharia Council (DSN).